Al-Farabi's heritage in A. Kassymzhanov's creative work is the beginning of national self-consciousness (Journal of Philosophy Culture and Political Science, 2018)
In this article  the creativity аl-Farabi as a basis of national self-consciousness in Kasymzhanov's philosophy considered (examined).